Islamic World Unity Through Developing Cross-Culture Communication and Religion - M. Arfah Shiddiq; M. Ishaq Shamad (Global Journal Al-Thaqafah, 2024)
Every one in every religion needs unity, peace and security in their daily life, especially in performing worship peacefully on this earth. It is not only for special worshipping, but also for interaction among human beings. The objective of this paper is to explore the development of cross-culture communication and religion. It is of human innate nature to possess skills in comunication with others. The experts on communication are really appreciative of the communication skills of human being because it very important to develop self-existence for continuous life, to acquire happiness, to avoid threat, especially in developing communication between culture and religion.